The theoretical basis and the empirical treatment of national innovation systems - Markus Balzat (Universität Augsburg, Institut für Volkswirtschaftslehre, 2002)
This paper deals with theoretical as well as empirical issues in research on national innovation systems (NIS). The aims of this paper are the following: first, some basic concepts of the NIS approach as they are used here are defined and explained. This seems to be necessary for reasons of clarity, since different authors in this field still make use of different concepts. Second, and based on this theoretical introduction, the empirical treatment of national innovation systems is discussed while recent trends in the NIS literature on performance measurement of innovation systems are summarized. Third, details of a research agenda with the goal to improve performance measurements of national innovation systems are given whilst potential pitfalls of benchmarking exercises in the context of national innovation systems are also discussed.
urn:nbn:de:bvb:384-opus4-712269
Keywords: O10; O30; P51; 330; innovation; national innovation systems; performance measurement